Electrical Transmission Systems and Smart Grids: Selected Entries from the Encyclopedia of Sustainability Science and Technology - Begovic M. M. Miroslav (Heidelberg, Springer, 2012)
Electric transmission networks are among the largest human-made engineering systems: For example, the transmission network in the United States covers over 300,000 km of lines and is served by 500 companies (electric utilities). In sharp contrast to the very incremental developments of the last century, transmission and control technologies experienced a major breakthrough at the beginning of the 21st century. The rapid growth of new energy generation technologies (renewables), significant advances in information processing applied to system monitoring, planning, operation, control, and protection, radical changes in distribution networks, and key shifts in end user behavior (advanced metering and control of demand response) have combined to produce the modern integrated electrical infrastructure commonly referred to as the smart grid.Featuring state-of-the-art, peer-reviewed entries from the Encyclopedia of Sustainability Science and Technology, this book provides a detailed introduction to select key topics which span energy technology, engineering, and urban planning. Worldwide experts discuss the integration of electric energy infrastructure into the broader critical infrastructures of the modern world and their various interdependencies. Dedicated chapters cover specific topics ranging from underground transmission and distribution, to energy and water interdependence, and their implications for urban areas. Coverage also includes the key role of new policy initiatives as catalysts of change.